Communications and information processing international conference, ICCIP 2012 Aveiro, Portugal, March 7-11, 2012 revised selected papers, Part I - Sha, Junpin; Zhao, Maotai (Communications in Computer and Information Science, 2012)
The two volume set, CCIS 288 and 289, constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Communications and Information Processing, ICCIP 2012, held in Aveiro, Portugal, in March 2012. The 168 revised full papers of both volumes were carefully reviewed and selected from numerous submissions. The papers present the state-of-the-art in communications and information processing and feature current research on the theory, analysis, design, test and deployment related to communications and information processing systems.